Genetically Engineered Frameshifted YopN-TyeA Chimeras Influence Type III Secretion System Function in Yersinia pseudotuberculosis - Amer, Ayad A. A. (Public Library of Science, 2013)

(untitled)
Type III secretion is a tightly controlled virulence mechanism utilized by many gram negative bacteria to colonize their eukaryotic hosts. To infect their host, human pathogenic Yersinia spp. translocate protein toxins into the host cell cytosol through a preassembled Ysc-Yop type III secretion device. Several of the Ysc-Yop components are known for their roles in controlling substrate secretion and translocation. Particularly important in this role is the YopN and TyeA heterodimer. In this study, we confirm that Y. pseudotuberculosis naturally produce a 42 kDa YopN-TyeA hybrid protein as a result of a +1 frame shift near the 3 prime of yopN mRNA, as has been previously reported for the closely related Y. pestis. To assess the biological role of this YopN-TyeA hybrid in T3SS by Y. pseudotuberculosis, we used in cis site-directed mutagenesis to engineer bacteria to either produce predominately the YopN-TyeA hybrid by introducing +1 frame shifts to yopN after codon 278 or 287, or to produce only singular YopN and TyeA polypeptides by introducing yopN sequence from Y. enterocolitica, which is known not to produce the hybrid. Significantly, the engineered 42 kDa YopN-TyeA fusions were abundantly produced, stable, and were efficiently secreted by bacteria in vitro. Moreover, these bacteria could all maintain functionally competent needle structures and controlled Yops secretion in vitro. In the presence of host cells however, bacteria producing the most genetically altered hybrids (+1 frameshift after 278 codon) had diminished control of polarized Yop translocation. This corresponded to significant attenuation in competitive survival assays in orally infected mice, although not at all to the same extent as Yersinia lacking both YopN and TyeA proteins. Based on these studies with engineered polypeptides, most likely a naturally occurring YopN-TyeA hybrid protein has the potential to influence T3S control and activity when produced during Yersinia-host cell contact.